(untitled) (Acta Horti Botanici Bucurestiensis, 2025)
This paper presents the list of alien plant species from Brăila County (Romania). The inventory is based on personal observations in the field in the last two years. The study has recorded 81 alien taxa who belong to 30 families, 36 of them beeing invasive. The Americas, Asia and the Mediterranean area are the main places of origin of the taxa of the inventory.